2020
DOI: 10.1155/2020/5019746
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Infiltration and Identifying Genes of Prognostic Value in the Papillary Renal Cell Carcinoma Microenvironment by Bioinformatics Analysis

Abstract: Papillary renal cell carcinoma (PRCC) is one of the most common histological subtypes of renal cell carcinoma. Type 1 and type 2 PRCC are reported to be clinically and biologically distinct. However, little is known about immune infiltration and the expression patterns of immune-related genes in these two histologic subtypes, thereby limiting the development of immunotherapy for PRCC. Thus, we analyzed the expression of 22 immune cells in type 1 and type 2 PRCC tissues by combining The Cancer Genome Atlas (TCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In our study, although not statically significant, pRCC2 expressed the highest median levels of CD163 (Figure 2) [34]. Consistent findings were seen at a transcriptomic level by Liu et al [35], based on CIBERSORT analysis, in which they found that M1 and M2 macrophages could predict pRCC2 clinical outcome. Thus, when creating a treatment plan for these cancer types, the pro-tumorigenic presence of M2 macrophages and the low expression levels of Tcell and B-cell markers should be considered.…”
supporting
confidence: 89%
“…In our study, although not statically significant, pRCC2 expressed the highest median levels of CD163 (Figure 2) [34]. Consistent findings were seen at a transcriptomic level by Liu et al [35], based on CIBERSORT analysis, in which they found that M1 and M2 macrophages could predict pRCC2 clinical outcome. Thus, when creating a treatment plan for these cancer types, the pro-tumorigenic presence of M2 macrophages and the low expression levels of Tcell and B-cell markers should be considered.…”
supporting
confidence: 89%
“…According to these characteristic variations, we further divided cluster A into subcluster A1 and A2 while cluster B into B1 and B2 and the differences of PD-L1, IFN-γ expression levels and immune cells infiltration rates were even greater between subcluster A1 and B1 ( Figures 2B and 3A ). Considering previous studies demonstrated M2 macrophages were negatively related to overall survival and CD8 + T cells played a major role in anti-tumor immunity ( 17 19 ), we thus defined subcluster A1 as high cytotoxic immune phenotype while subcluster B1 as low cytotoxic immune phenotype. In our data, the contents of CD8 + T cells are negatively correlated with those of Macrophages M2, while in several previous studies the contents of CD8 + T cells were believed to predict a better survival benefit in multiple tumor types, Macrophages, however, in the opposite side ( 20 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…CCL19 is a critical component of an immune-related prognostic classifier for the prognostic evaluation of patients with papillary renal cell carcinoma ( Wang et al, 2021 ). In addition, the CCL19/CCR7 axis could be a promising target for tumor gene therapy in type 2 papillary renal cell carcinoma according to Liu et al ’s report ( Liu et al, 2020 ). All the evidence demonstrates that CCL19 might be a critical biomarker and therapeutic target in human kidney diseases.…”
Section: Discussionmentioning
confidence: 99%